2017
DOI: 10.3389/fpsyg.2017.01517
|View full text |Cite
|
Sign up to set email alerts
|

Implementing the TARGET Model in Physical Education: Effects on Perceived Psychobiosocial and Motivational States in Girls

Abstract: Grounded in achievement goal and self-determination theories, the purpose of this study was to investigate the effects of mastery and performance climate interventions on students’ psychobiosocial (PBS) states and self-determined motivation. A first study was conducted to determine the validity of the measures. In a second study, two groups of female students (N = 65, 14–15 years of age) took part in the investigation. A mastery-performance group participated in eight task-involving lessons and then in another… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 72 publications
4
30
0
1
Order By: Relevance
“…All other included studies did not provide sufficient information on outcome assessment but at least partially mitigated a possible distortion by usually using valid instruments and questionnaires. Potential attrition bias results from incomplete follow-up or losses in follow-up that are inadequately taken into account: six NRESs (Morgan and Carpenter, 2002;Jaakkola and Liukkonen, 2006;Viciana et al, 2007; Erturan-lker and Demirhan, 2013; Abós et al, 2016;Bortoli et al, 2017) and three LSs (Braithwaite et al, 2011;Halvari et al, 2011;Warburton and Spray, 2013) showed appropriate treatment of drop-outs. For all RCTs and the majority of the NRESs, drop-outs of participants remained unclear, thus leaving room for biasing differences between initial and ending samples.…”
Section: Methodological Quality and Risk Of Biasmentioning
confidence: 99%
See 4 more Smart Citations
“…All other included studies did not provide sufficient information on outcome assessment but at least partially mitigated a possible distortion by usually using valid instruments and questionnaires. Potential attrition bias results from incomplete follow-up or losses in follow-up that are inadequately taken into account: six NRESs (Morgan and Carpenter, 2002;Jaakkola and Liukkonen, 2006;Viciana et al, 2007; Erturan-lker and Demirhan, 2013; Abós et al, 2016;Bortoli et al, 2017) and three LSs (Braithwaite et al, 2011;Halvari et al, 2011;Warburton and Spray, 2013) showed appropriate treatment of drop-outs. For all RCTs and the majority of the NRESs, drop-outs of participants remained unclear, thus leaving room for biasing differences between initial and ending samples.…”
Section: Methodological Quality and Risk Of Biasmentioning
confidence: 99%
“…Six studies compared two or more intervention groups and had no control group (Solmon, 1996;Standage et al, 2007;Viciana et al, 2007;Erturan-lker and Demirhan, 2013;Erturan-Ilker, 2014;Logan et al, 2014). Two studies used within-subject designs: Bortoli et al (2017) compared two experimental groups that received consecutively both a mastery and a performance climate intervention but in reverse sequence, and Papaioannou and Kouli (1999) compared a lesson with mastery-involving tasks with a lesson with performance-involving tasks. The duration of the interventions largely varied across studies.…”
Section: Intervention Studiesmentioning
confidence: 99%
See 3 more Smart Citations